Habermas, Religion, and Citizenship. Issue 2 (13th November 2013) - Neal, Patrick
Abstract What is the appropriate place for religious argument in the public realm of a liberal-democratic polity? The primary competing positions have been a "liberal" account and a "revisionist" response arguing for a greater role for religious argument in liberal democracy than the liberal position is ordinarily understood to allow. Liberals and their revisionist critics disagree about whether restraints on religious arguments and justifications are justified and desirable. Jürgen Habermas has intervened in this debate with a provocative account of the place of religion in the public sphere. Habermas presents his account as an alternative to both the liberal and the revisionist perspectives, and purports to do justice to the legitimate claims of each without falling prey to the failings of either. This article critically analyzes Habermas's interesting proposal and argues that it does not succeed.